DAMPAK PENGEMBANGAN DESA WISATA DALAM MENINGKATKAN PEREKONOMIAN MASYARAKAT LOKAL DESA MALANGGA KECAMATAN GALANG KABUPATEN TOLITOLI - Kasim, Fitri S.; Satriani, Rifa (Ekonis: Jurnal Ekonomi dan Bisnis, 2024)
Abstract : This study aims to determine the impact of tourism village development on employment opportunities, income and prices of basic needs of the village community in Malangga. The research method used in this research is descriptive qualitative. From the results of field research, it is known that the development of tourism village development in Malangga Village, the village government conducts various promotions of tourism potential owned by Malangga Village, so that it has a positive impact on the local community, where there are new business opportunities in providing employment opportunities for the community. In addition, the tourism potential owned by Malangga Village also has a positive impact on the local community, where there is an increase in local community income, an increase in the price of local community products in the form of palm sugar, and does not have an impact on the price of basic necessities, but there is still a need for development in improving the human resources of tourism village managers, this requires attention from the government and the local community as managers of tourism villages.Keywords : Economic Impact, Tourism Village, Local Communities.